Volatile compounds and microbial development in sonicated cloudy apple juices: preliminary results. Issue 1 (2nd January 2016) - Bastianello, E.; Montemurro, F.; Fasolato, L.; Balzan, S.; Marchesini, G.; Contiero, B.; Cardazzo, B.; Novelli, E.
Abstract : Two studies (storage and challenge tests) investigated the microbial shelf life combined with a semi-quantitative determination of volatile compounds of cloudy apple juices after power ultrasound (US) treatment. The sublethal injury of spoiler yeasts ( Candida parapsilosis and Rhodotorula glutinis ) was also evaluated. The maximum effect of sonication was observed 14 days post-treatment in both tests, especially on psychrotrophic count. Sublethal injury occurred only in C. parapsilosis . Microbiological data estimated the shelf life of sonicated juices to be around 21 days. The typical aroma compounds of the raw juices decreased quickly in control samples compared with sonicated ones. The flavor stability provided by US treatment seemed to be maintained for at least the first 14 days of cold storage. The US affected the shelf life of raw apple juices, probably due to yeast sublethal stress; some specific aroma compounds could be used as freshness or treatment markers.